I have the linear PDE

$$yu_x - xu_y = 0 \qquad x^2 + y^2 < a^2 \\ u(0,y) = (a^2-y^2)^{\frac{1}{2}} \qquad y \in(-a,a)$$

where $a > 0$ is a constant.

So what I have done is to say that

$$a_1 = y \quad a_2=-x \quad b=0 \\ \gamma(x_0(s), y_0(s)) = \gamma(0,s) = (a^2-s^2)^{\frac{1}{2}}$$

with $\gamma(0,s)$ being the Cauchy curve.

From this I say that

$$\widetilde{x}_\tau = \widetilde{y} \qquad \widetilde{x}(0,s) = 0 \\ \widetilde{y}_\tau = -\widetilde{x} \qquad \widetilde{y}(0,s) = s \\ \widetilde{z}_\tau = 0 \qquad \widetilde{z}(0,s) = (a^2-s^2)^{\frac{1}{2}}$$

Now I see that

$$ \widetilde{x}_{\tau\tau} = \widetilde{y}_\tau = -\widetilde{x}$$

this gives

$$\widetilde{x} = A\,cos(\tau) + B\,sin(\tau)$$

and from the initial boundary condition it can be shown that $A=0$. Similarly,

$$ \widetilde{y}_{\tau\tau} = \widetilde{x}_\tau = -\widetilde{y}$$


$$\widetilde{y} = C\,e^{\tau} + B\,e^{\tau}$$

which using the boundary condition gives

$$s = C + D$$

now I know I have made a mistake somewhere because I get stuck here. I don't know how to find the values of $B,\, C,\,D$. But I don't know what I ahve done wrong.

I know that there is a second method where you multiply $x_\tau$ and $y_\tau$ together but I don't want to do it that way.


$$yu_x-xu_y=0$$ $$\frac{\partial u}{x\partial x}-\frac{\partial u}{y\partial y}=0$$ With $X=x^2$ and $Y=y^2$ : $$\frac{\partial u}{\partial X}-\frac{\partial u}{\partial Y}=0$$ The general solution is well known : $$u=F(X+Y)$$ $$u(x,y)=F(x^2+y^2) \tag 1$$ $F$ is an arbitrary differentiable function, to be determined according to the boundary condition.

Condition : $\quad u(0,y)=\sqrt{a^2-y^2}$ $$F(0^2+y^2)=\sqrt{a^2-y^2}$$ Let $X=y^2$ $$F(X)=\sqrt{a^2-X}$$ Now, the function $F(X)$ is determined. We put it into the above general solution Eq.$(1)$, where $X=x^2+y^2$. Thus $F(x^2+y^2)=\sqrt{a^2-(x^2+y^2)}$ $$u(x,y)=\sqrt{a^2-(x^2+y^2)}$$

  • $\begingroup$ Wow. This is a completely different way to what I've ever seen before $\endgroup$ – Gragbow May 10 '18 at 16:03

Even with your method it should work

$$ \begin{cases} yu_x - xu_y = 0 \qquad x^2 + y^2 < a^2 \\ u(0,y) = (a^2-y^2)^{\frac{1}{2}} \qquad y \in(-a,a) \end{cases} $$ $$dz=0 \implies z=c_2$$ For the second integral curve $$\frac {dx}{y}=\frac {dy}{-x} \implies -xdx-ydy=0$$ $$ \implies -\frac {x^2}2-\frac {y^2}2=c_1 \implies {x^2}+ {y^2}=c_1 $$ $$f(c_1)=c_2 \implies f(x^2+y^2)=z$$ Therefore $$u(x,y) =f(x^2+y^2)$$ with IC we have that $$u(0,y) =f(y^2)=(a^2-y^2)^{1/2}$$ So that $$u(x,y) =(a^2-y^2-x^2)^{1/2}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.